Some doubts about in vitro eugenics as a human enhancement technology - Siegel, Andrew W (Journal of medical ethics, 2014)
[...]while Sparrow correctly observes that the issues about safety and risk in testing in vitro eugenics with human subjects are similar to those that arose in testing IVF with humans, it does not follow that we should view the risks as equally acceptable in both cases.